Effects of nanoselenium supplementation on lactation performance, nutrient digestion and mammary gland development in dairy cows - Yapeng Liu; Jing Zhang; Lijun Bu; Wenjie Huo; Caixia Pei; Qiang Liu (Animal Biotechnology)
The objective of this experiment was to evaluate the influence of nanoselenium (NANO-Se) addition on milk production, milk fatty acid synthesis, the development and metabolism regulation of mammary gland in dairy cows. Forty-eight Holstein dairy cows averaging 720 ± 16.8 kg of body weight, 66.9 ± 3.84 d in milk (dry matter intake [DIM]) and 35.2 ± 1.66 kg/d of milk production were divided into four treatments blocked by DIM and milk yields. Treatments were control group, low-Se (LSe), medium-Se (MSe) and high-Se (HSe) with 0, 0.1, 0.2 and 0.3 mg Se, respectively, from NANO-Se per kg dietary dry matter (DM). Production of energy- and fat-corrected milk (FCM) and milk fat quadratically increased (p < 0.05), while milk lactose yields linearly increased (p < 0.05) with increasing NANO-Se addition. The proportion of saturated fatty acids (SFAs) linearly decreased (p < 0.05), while proportions of monounsaturated fatty acids (MUFAs) linearly increased and polyunsaturated fatty acids (PUFAs) quadratically increased. The digestibility of dietary DM, organic matter (OM), crude protein (CP), neutral detergent fiber (NDF) and acid detergent fiber (ADF) quadratically increased (p < 0.05). Ruminal pH quadratically decreased (p < 0.01), while total VFA linearly increased (p < 0.05) with increasing NANO-Se addition. The acetic to propionic ratio decreased (p < 0.05) linearly due to the unaltered acetic molar percentage and a quadratical increase in propionic molar percentage. The activity of CMCase, xylanase, cellobiase and pectinase increased linearly (p < 0.05) following NANO-Se addition. The activity of α-amylase increased linearly (p < 0.01) with an increase in NANO-Se dosage. Blood glucose, total protein, estradiol, prolactin, IGF-1 and Se linearly increased (p < 0.05), while urea nitrogen concentration quadratically decreased (p = 0.04). Moreover, the addition of Se at 0.3 mg/kg from NANO-Se promoted (p < 0.05) mRNA and protein expression of PPARγ, SREBP1, ACACA, FASN, SCD, CCNA2, CCND1, PCNA, Bcl-2 and the ratios of p-ACACA/ACACA and BCL2/BAX4, but decreased (p < 0.05) mRNA and protein expressions of Bax, Caspase-3 and Caspase-9. The results suggest that milk production and milk fat synthesis increased by NANO-Se addition by stimulating rumen fermentation, nutrients digestion, gene and protein expressions concerned with milk fat synthesis and mammary gland development.